2016
DOI: 10.1139/cjss-2015-0072
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Ontario P index recommendations for reduced manure and fertilizer phosphorus applications on corn yields and soil phosphorus

Abstract: Environmental indices for soil P limit P applications when soil tests and risk of P losses exceed a given threshold. Producers' reluctance to reduce P inputs often stem from concerns regarding reduced crop production and soil fertility. Our objectives were to identify changes in soil P fractions after 4 yr of repeated manure or fertilizer P applications at rates ≤ crop removal by corn (Zea mays L.), and the impact of these applications on yields. Olsen P and soil P fractions extracted using a modified Hedley P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…Maintaining the same stocking rate throughout, winter spring wool growth decreased by 28%. In contrast to pasture, other studies have found little or no decrease in maize (Zea mays L.) production as STP concentrations and WEP trend toward their respective targets (Zhang et al, 2004;Ribey and O'Halloran, 2016). This is presumably due to the ability of maize to explore a much greater depth and volume of soil than pasture and therefore access greater P reserves.…”
Section: Meeting Environmental Targetsmentioning
confidence: 93%
“…Maintaining the same stocking rate throughout, winter spring wool growth decreased by 28%. In contrast to pasture, other studies have found little or no decrease in maize (Zea mays L.) production as STP concentrations and WEP trend toward their respective targets (Zhang et al, 2004;Ribey and O'Halloran, 2016). This is presumably due to the ability of maize to explore a much greater depth and volume of soil than pasture and therefore access greater P reserves.…”
Section: Meeting Environmental Targetsmentioning
confidence: 93%
“…Soil samples were air dried, sieved (2 mm), and extracted using the Olsen P procedure. Phosphorus concentration was analyzed using the molybdate blue method with a Lachat QuickChem FIA+ Auto-Analyzer (8000 Series, Lachat Instruments, Loveland, CO, USA) [51][52][53].…”
Section: Yield Determination and Soil And Plant Sampling For P Analysesmentioning
confidence: 99%
“…The direct implication is that soil P saturation was not evaluated, which is an important factor to consider when evaluating the impact of the subsidy. While monitoring soil P saturation is relevant for environmental safety (Ketterings and Czymmek, 2012;Ribey and O'Halloran, 2016;Williams et al, 2015), continuous monitoring campaigns for this variable in Chile are absent.…”
Section: Effectivity Of a P Fertilization Subsidy: The Case Studymentioning
confidence: 99%